2021
DOI: 10.3389/fphys.2021.637629
|View full text |Cite
|
Sign up to set email alerts
|

Role of 25-Hydroxyvitamin D3 and 1,25-Dihydroxyvitamin D3 in Chicken Embryo Osteogenesis, Adipogenesis, Myogenesis, and Vitamin D3 Metabolism

Abstract: A study was conducted to understand the effects of 25-hydroxyvitamin D3 (25OHD) and 1,25-dihydroxyvitamin D3 (1,25OHD) administration on the expression of key genes related to osteogenesis, adipogenesis, myogenesis, and vitamin D3 metabolism in the chicken embryo. A total of 120 fertilized Cobb 500 eggs were used in the current study and were reared under standard incubation conditions. On embryonic day 3 (ED 3), PBS (C), PBS with 40ng 1,25OHD (1,25D-L), 200ng 1,25OHD (1,25D-H), 40ng 25OHD (25D-L), or 200ng 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…Our results show that Myf5 mRNA expression is significantly lower in 1,25(OH) 2 D 3 treated cells than controls on day 1, possibly indicating a faster down regulation of early differentiation markers, which may suggest that cells are differentiating more quickly. These results are in agreement with previous work which found a decrease in Myf5 gene expression just 6 h post 1,25(OH) 2 D 3 injection in chick embryos ( Chen et al, 2021 ). In addition, work in C2C12 cells showed that both inactive [25(OH)D 3 ] and active VD treatment reduced Myf5 mRNA expression ( Girgis et al, 2014 ).…”
Section: Discussionsupporting
confidence: 94%
“…Our results show that Myf5 mRNA expression is significantly lower in 1,25(OH) 2 D 3 treated cells than controls on day 1, possibly indicating a faster down regulation of early differentiation markers, which may suggest that cells are differentiating more quickly. These results are in agreement with previous work which found a decrease in Myf5 gene expression just 6 h post 1,25(OH) 2 D 3 injection in chick embryos ( Chen et al, 2021 ). In addition, work in C2C12 cells showed that both inactive [25(OH)D 3 ] and active VD treatment reduced Myf5 mRNA expression ( Girgis et al, 2014 ).…”
Section: Discussionsupporting
confidence: 94%
“…The stability of housekeeping genes were confirmed by their consistent Ct values among the treatments (P > 0.1) 119 . BGLAP, RUNX2, SPP1, BMP2, and ALP were used as genetic markers of bone formation in the bone marrow 120 . NFKB, RANKL, FOS, ACP5, NFATC1, IL1B, TNF, SMAD1, and TNFRSF11B (OPG) 121 were used as the genetic markers for osteoclastic activity in the bone marrow.…”
Section: Real-time Quantitative Pcr Analysis Of Gene Expression In Bo...mentioning
confidence: 99%
“…Various studies have shown that there are several possible injection sites: air cell, amniotic sac, directly into the chicken embryo, or yolk sac [ 92 , 93 , 94 , 95 ]. The preferred site for in ovo injection in the early stages of embryo development is the air cell, but for injections of vaccines and nutrients, the best time is around day 18 of egg incubation [ 88 ].…”
Section: Avian Cell Culture Models For Testing Immunomodulatory Effec...mentioning
confidence: 99%